Doxorubicin-mediated testicular toxicity is associated with dysregulated mTOR/Beclin-1 pathways, oxidative stress, inflammation and apoptosis in Wistar rats: preventive role of lutein - Jennifer Efe Jaiyeoba-Ojigho; Jerome Ndudi Asiwe; Joseph Chimezie; Blessing Oluwakemi Abe; Oghenemarho Monalisa Ataikiru; Taniyohwo Mamerhi Enaohwo; Alexander Obidike Naiho; Lilian Ebele Chris-Ozoko; Godstime Jesukobiruo Ibada; Sylvester Ifeakachukwu Okuepusu; Favour Isioma Ikukaiwe; Winnie Taiye Ogwu (Laboratory Animal Research)
Abstract Background Lutein offers undoubted hope for preventing doxorubicin uncharacteristic reproductive function which remains a worldwide health concern in cancer chemotherapy. However, the mechanisms underlying the effect of lutein on maintaining the male reproductive milieu have not yet been fully identified. The current study investigates the preventive effect of lutein in doxorubicin-induced testicular toxicity. Methods Twenty male Wistar rats were randomly assigned into four groups of five animals (n = 5) and were pretreated with lutein (40 mg/kg i.p) prior to doxorubicin treatment (15 mg/kg i.p). Following the end of the experiment, animals were euthanized and the testes were collected and processed for semen and biochemical analysis. Results The results revealed that exposure to doxorubicin caused hormonal imbalance, reduced semen quality and elicited oxidative stress, inflammatory reactions, apoptosis as well as dysregulation of autophagic process which was accompanied by fibrosis and histomorphological aberrations. Interestingly, pretreatment with lutein significantly restored hormonal balance and protected against the adverse effects of doxorubicin. Conclusions The findings of this study showed that lutein prevents doxorubicin-mediated testicular toxicity via modulation autophagic pathways accompanied with inhibition of oxidative stress, inflammation and apoptosis.